Deiktinės sistemos baltų kalbų tarmėse - Rosinas, Albertas (Baltistica, 1982)
Deictic systems in Baltic dialects The article is an attempt to investigate the Baltic deictic systems and to present the motivation of their systematic restructuring. The following conclusions can be drawn: 1. Binomial deictic systems appear to predominate in Baltic dialects. 2. The binomial deictic systems (as well as the one-member system in the Samogitian dialect) derive from three-member systems. 3. The reconstruction of the common Baltic three-member deictic protosystem could be considered valid if it were to be assumed that the pronoun *vin(E) (j)is → viņš “that” had been early substituted for the Proto-Latvian pronoun *anas (cf. o-trs “second” < *an-taras). 4. Diachronically Lithuanian and Prussian stand in closer affinity to each other than to Latvian; the latter possesses a different pronoun to indicate non-proximity in its three-member deictic system. 5. Synchronically the Latgalian and the Lithuanian East Highland (Aukštaičiai) subdialects are, however, in closer affinity to each other; they are characterized by structurally similar binomial deictic systems, cf. Lat. itys / tys and Lith. itas / tas. 6. The Lithuanian Samogitian dialect and some Latvian Liiv subdialects come close by their one-member deictic systems. 7. The marked members of modern deictic systems, such as Lith. šitas, itas, Lat. šitas, itys, sitȩntas, šitȩnais, are independent derivatives of individual Baltic dialects. The derivatives in question appeared in dialects after the phonological changes in word-final position. 8. New deictic systems of demonstrative pronouns can be formed by: a) combining a demonstrative word (local adverb) with a demonstrative pronoun, e.g. Lat. *it(E) “here” + ti/ys → iti/ys, Lith. it(ai) or *it(E) “here” + tas → itas, Lat. šitȩn “here” + tas → šitȩntas, *šitȩnE “here” + (j)is → šitȩnais, šitȩneis; b) combining stems of two demonstrative pronouns of a similar deictic meaning, e.g. Lith. ši- + tas → šitas “this”. 9. Typologically the Prussian language and the Western dialects of East Baits, characterized by binomial deictic systems, approach the Finno-Ugrian languages which have binomial deictic systems as well, cf. Lat. šis / tas (Puze, Skrunda), Pruss. schis / stas and Est. see / too. 10. The binomial deictic systems of the Baltic Eastern dialects are structurally similar to those of the East Slavonic languages, cf. Lat. itys j tys, Lith. itas / tas and Russ. этот / mom, Byeloruss. гэтот / тот, йэтот / mom. 11. The Samogitian dialect and some Liiv subdialects are typologically similar to the Liiv and the Swedish languages by their one-member deictic systems, cf. Liiv sìe, Lat. and Sam. tas, Sw. den. The opposition proximity / non-proximity is expressed by the words “here”/“there”, cf. Sam. šitã˙- tas “this”/untã˙ tàs “that”, Lat. tas te “this”/tas tur “that” and Sw. Derme boka her er bedre enn den boka der.